2020
DOI: 10.1111/adj.12777
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings detected on cone beam computed tomography in an older population for pre‐implant assessment

Abstract: Objectives: The aim of this retrospective study was to record incidental findings in CBCT scans taken in an older population for pre-implant assessment, and to examine whether these findings would influence the intended dental implant placement. Methods: 300 consecutive CBCT scans over the age of 40 years was carried out. The incidental findings were grouped into regions as follows: dentoalveolar structures, maxilla and mandible, paranasal sinuses, temporomandibular joint (TMJ), naso/oral-pharyngeal airway, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Lopes et al [16] detected an average of 4.72 incidental findings in a total of 47 examinations that covered both the mandible and the maxilla. Nguyen et al found an average of 1.85 IF per scan in 555 patients of an older population for pre-implant assessment [17]. In this context, the aim of this study was the systematic analysis of a large consecutive patient group with regard to the frequency and especially the clinical impact of incidental findings depending on the indication for CBCT imaging and the size of the FOV.…”
Section: Introductionmentioning
confidence: 99%
“…Lopes et al [16] detected an average of 4.72 incidental findings in a total of 47 examinations that covered both the mandible and the maxilla. Nguyen et al found an average of 1.85 IF per scan in 555 patients of an older population for pre-implant assessment [17]. In this context, the aim of this study was the systematic analysis of a large consecutive patient group with regard to the frequency and especially the clinical impact of incidental findings depending on the indication for CBCT imaging and the size of the FOV.…”
Section: Introductionmentioning
confidence: 99%
“…Benzer çalışmalarda da rastlantısal bulguların hasta başına düşen sayısının çalışmamıza kıyasla daha fazla olduğu görülmektedir. 17,18,19 Bizim çalışmamızda bu sayının düşük olmasının en önemli sebebi, çalışmamıza dahil edilecek KIBT görüntüleri belirlenirken, istek notlarında implant planlaması dışında, gömülü diş, odontojenik-non odontojenik lezyon vb. durumlar belirtilmişse bu hastaların görüntülerinin çalışma dışı bırakılmış olmasıdır.…”
Section: Discussionunclassified
“…Literatürde TME bulgularının incelendiği çalışmalarda kondiler erezyon, osteofit ve bifid kondil bulgularının oranı %8-10 iken bizim çalışmamızda bu oranın biraz daha yüksek (%12.5) olduğu gözlenmiştir. 6,17,24 Bu farkın literatürdeki çalışmaların daha çok panoramik görüntüler üzerinde yapılmış olması ve KIBT'ın panoramik görüntülere göre TME bölgesini analiz etmedeki üstünlüğünden kaynaklı olduğu düşünülmektedir.…”
Section: Discussionunclassified
“…Unfortunately, many dental clinicians lack the training necessary for the interpretation of IFs. To investigate this concern, Nguyen et al 212 conducted a retrospective analysis of IFs in CBCT scans made for older patients during dental implant treatment assessment, and to determine whether these IFs influenced the intended dental implant therapy. The authors defined an IF as one outside of the clinical focus of the CBCT examination and otherwise not known clinically or not detected with plain film imaging (bitewing, periapical, and/or panoramic imaging).…”
Section: General Implant Prosthodontic Considerationsmentioning
confidence: 99%